ANALISIS NILAI PENDIDIKAN DALAM NOVEL “HABIBIE & AINUN” KARYA B.J HABIBIE - Risma Herawati; Andri Andri; Yusep Ahmadi F (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The making of this article aims to examine and know the values that educate after reading the novel "Habibie & Ainun" by B.J Habibie. With the formulation of the problem in it: what educational values are there in the novels "Habibie & Ainun"? The message of the value of education as an indicator of this research are moral values, religious values, nationalism values, patriotism values, and romantic values in the family. The method used is a qualitative descriptive method with the technique of reading and writing important things, meaning that the researcher looks for data by reading the novel to find out the educational value contained in it. This novel by B.J Habibie is analyzed through signs in a sentence, paragraph, and quote dialog. The researcher uses the method that is easier to understand according to the conditions of the novel based on theory. The results of the study show that the novel "Habibie & Ainun" has educational values: moral, religious, tolerance, a spirit of nationalism, patriotism and true love.